2015
DOI: 10.1123/ijsnem.2014-0134
|View full text |Cite
|
Sign up to set email alerts
|

The Ingestion of 39 or 64 g·hr−1 of Carbohydrate is Equally Effective at Improving Endurance Exercise Performance in Cyclists

Abstract: In an investigator-blind, randomised cross-over design, male cyclists (mean±SD) age 34.0 (± 10.2) years, body mass 74.6 (±7.9) kg, stature 178.3 (±8.0) cm, peak power output ( (95% CI -8.8 to 1.5%). No further differences between CHO trials were reported. No interaction between CHO dose and pacing strategy occurred. 39 and 64g·h -1 of CHO were similarly effective at improving endurance cycling performance compared to a 0g·h -1 control in our trained cyclists.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
19
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 22 publications
1
19
1
Order By: Relevance
“…However, one must cautiously explore this approach as to avoid overwhelming the gastrointestinal system potentially leading to cramping and discomfort once exercise begins. In this respect one should consider the findings of Newell et al [ 55 ] who had 20 well-trained, experienced cyclists perform four different feeding conditions (no carbohydrate [0 g/h] control, 20 g/h, 39 g/h or 64 g/h) throughout completion of a two-hour cycling bout at 95% lactate threshold (185 ± 25 watts) followed by completion of a standardized time trial. When carbohydrates were ingested at a dosage of 39 or 64 g/h, time trial performance was significantly improved compared to the control group.…”
Section: Introductionmentioning
confidence: 99%
“…However, one must cautiously explore this approach as to avoid overwhelming the gastrointestinal system potentially leading to cramping and discomfort once exercise begins. In this respect one should consider the findings of Newell et al [ 55 ] who had 20 well-trained, experienced cyclists perform four different feeding conditions (no carbohydrate [0 g/h] control, 20 g/h, 39 g/h or 64 g/h) throughout completion of a two-hour cycling bout at 95% lactate threshold (185 ± 25 watts) followed by completion of a standardized time trial. When carbohydrates were ingested at a dosage of 39 or 64 g/h, time trial performance was significantly improved compared to the control group.…”
Section: Introductionmentioning
confidence: 99%
“…Tests with commercial sports drinks prove (Newell et al, 2015;Roberts et al, 2012) or disprove (Burke et al, 2005;Coletta et al, 2013;Qin et al, 2017;van Nieuwenhoven et al, 2005) the ergogenic effects. Coombes and Hamilton (2000) concluded in their tests that no isotonic sports drinks currently on the market are superior to any other.…”
Section: Introductionmentioning
confidence: 99%
“…These authors reported a non-significant but ‘likely’ 2.3% improvement in performance when comparing 60 vs. 30 g·h −1 suggesting a dose-response effect of CHO feeding rate. We recently reported that a 2.3% performance gain would not necessarily be ‘likely’ due to typical variance observed in performance outcome measures [ 7 ] when using a more suitably powered design. In addition, there has yet to be an extensive exploration of the association between multiple metabolic variables and subsequent exercise performance outcomes using a dose-response investigation.…”
Section: Introductionmentioning
confidence: 99%